Evaluation Of Emulsion Liquid Membrane On Pharmaceutical Waste From Aquaculture Wastewater - Jasni, Mohd Khairul Akmal (Universiti Sains Malaysia, 2021)
Liquid membrane technology is undergoing a significant increase in both research and application as an industrial separation method at the moment. A liquid membrane can be used to isolate a specific solute from a mixture and even extract a solute against its concentration gradient. There are three liquid phases in a liquid membrane system: feed phase, liquid membrane organic phase, and receiving phase. Either a supported liquid membrane or an emulsion (unsupported) liquid membrane can be made. Emulsion liquid membranes are liquid membranes that disseminate the emulsion's membrane phase into the feed phase to be treated. This method was investigated as an alternative process for the recovery of ibuprofen from pharmaceutical waste. The formulations of ELM were studied in order to find the most suitable component. Besides that, some parameter affecting the performance of ELM was also being studied. The parameter involved are agitation speed, emulsifying time, concentration of stripping agent, internal to membrane ratio, and the weight percentage of surfactant and carrier. Based on the result, the most suitable component for ELM was found to be kerosene as diluent, trioctylamine as carrier, and ammonia as stripping agent. It is also being found that, the optimal condition for this emulsion liquid membrane study was obtained at 300 rpm of agitation speed, 15 minutes of emulsification time, a ratio of 1:3 internal to membrane, 0.1 M concentration of stripping agent, and 6 wt% and 2wt% for the weight percentage of carrier and surfactant respectively which yield 84% of efficiency.